2018
DOI: 10.1097/md.0000000000011524
|View full text |Cite
|
Sign up to set email alerts
|

Factors related with osteoporosis treatment in postmenopausal women

Abstract: Although fractures had high mortality and morbidity, many studies proved that fracture risk might be decreased by pharmacological therapy, although a low treatment adherence rate is observed. The aim of this study was to identify factors associated with osteoporosis treatment in postmenopausal women.A cross-sectional study was carried out from March to August 2013 at the primary care setting. Postmenopausal women were recruited. A standardized questionnaire was applied. Women who were using at least one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
0
26
0
3
Order By: Relevance
“…General information collected for all subjects included: (i) BMD of the lumbar spine and hip; (ii) BTM: PINP, β‐CTX, and N‐MID; (iii) bone metabolism‐related indicators, ALP, Ca, and P. BMD was were measured using DXA (enCORE, General Electric, version 15), instrument quality control was carried out before measurement, and those subjects with T < −2.5 SD were diagnosed as having osteoporosis according to diagnosis criteria. BMDL and BMDH represent BMD of the lumbar and the total hip, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…General information collected for all subjects included: (i) BMD of the lumbar spine and hip; (ii) BTM: PINP, β‐CTX, and N‐MID; (iii) bone metabolism‐related indicators, ALP, Ca, and P. BMD was were measured using DXA (enCORE, General Electric, version 15), instrument quality control was carried out before measurement, and those subjects with T < −2.5 SD were diagnosed as having osteoporosis according to diagnosis criteria. BMDL and BMDH represent BMD of the lumbar and the total hip, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Scholars have suggested that DXA should be used as a tool for the diagnosis of osteoporosis, and the threshold value for the diagnosis of osteoporosis is T value <−2.5 SD. Although race, region, fracture history, hormones, and other factors may affect the occurrence of OF, OF risk assessment based on BMD is also recommended.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A relevant aspect to be considered is that of possible pharmacologic treatment interruptions due to unwanted discontinuation of BMD testing caused by COVID-19 lockdown, as DXA remains the most commonly used technique for BMD evaluation [16]. It has been reported that BMD testing is associated to increased adherence to osteoporosis pharmacologic treatment, since its execution probably increase patients' awareness of osteoporosis risk, when the disease is diagnosed [17,18]. Future studies will certainly focus on this important topic when densitometric activity will return to pre-pandemic standards.…”
Section: Discussionmentioning
confidence: 99%
“…[56] The social burden of fractures will increase throughout the world as the population ages, so the prevention of primary and secondary OFs is essential. [789] Fortunately, OFs are preventable and their understanding of the epidemiology could help us focus efforts on the patients at greatest risk. In addition, it is very important to recognize the risk of secondary fractures that may occur after initial OFs.…”
Section: Introductionmentioning
confidence: 99%